Pelatihan Pengetahuan Dan Keterampilan Menggunakan Alat Ukur Waterpass Untuk Peningkatan Kompetensi Siswa Kelas X Jurusan Teknik Konstruksi dan Perumahan SMKN 1 Rengat Barat Kabupaten Indragiri Hulu - Nedra Neswita; Sahriyal Sahriyal; Sri Agustin; Arif Sudaryanto; Bobby Mauliantino; Yelfidar Yelfidar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this community service activity is to train and guide the skills of students of West Rengat 1 Vocational School in an effort to increase competence in knowledge, skills and processing of measurement data using a waterpass measuring instrument in soil surveying subjects, because one of the competencies that must be possessed SMK students, especially those majoring in construction and housing engineering, are studying land surveying using a waterpass tool. The methods used in this training activity include presentation, demonstration, practice and evaluation. The results of the evaluation of this activity were obtained from the assignments given to each student. The instructor checks the calculated measurement results. From the initial observation to the final evaluation process, it was found that there was an increase in the knowledge and skills of the students. Initially the participants did not have the ability to do surveying using a waterpass, but after the training was given the participants were able to apply the program. The evaluation results showed that as many as 67% of the participants were able to carry out the measurement assignments that had been given.